1/7 (x - 3) = 5/7
1/7x - 3/7 = 5/7
1/7x - 3/7 + 3/7 = 5/7 + 3/7
1/7x = 8/7
1/7x(7) = 8/7(7)
X = 56/7
X = 8
Step-by-step explanation:
the answer is B. y (4 + z)
Option C: is the product of the rational expression.
Explanation:
The given rational expression is
We need to determine the product of the rational expression.
<u>Product of the rational expression:</u>
Let us multiply the rational expression to determine the product of the rational expression.
Thus, we have;
Let us use the identity in the above expression.
Thus, we get;
Simplifying the terms, we get;
Thus, the product of the rational expression is
Hence, Option C is the correct answer.
Answer:
It is already rounded to the nearest tenth! Hope this helps!
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
it's more a gut feeling